THE INFLUENCE OF GREEN MARKETING STRATEGY ON PURCHASING DECISIONS WITH EMOTIONAL DESIRE AS A MODERATING VARIABLE - Muhammad Amsal Nasution; Muhamad Risal Tawil; Kushariyadi; Jeffri Wuisan Lontaan Gumerung; Lenda Lumentah (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Backgrounds: Researchers believe that a marketing strategy that pays attention to and prioritizes environmental protection aspects can attract the attention of the public, especially environmental observers, those who care about the environment, and so on, to decide to purchase the products we offer by paying attention to environmental aspects. ObjectivesTherefore, this research aims to analyze the influence of Green Marketing Strategy on Purchasing Decisions. Different from previous research, this research adds the Emotional Desire variable as a moderating variable which researchers can strengthen the influence of the Green Marketing Strategy variable on purchasing decisions. Methods: This research is quantitative research with an explanatory approach. This research obtained data by distributing questionnaires digitally to 100 producers and 200 consumers who had been involved in the TikTok shop for at least 1 month. The questionnaire contains 8 question items consisting of 4 question items for the Green Marketing Strategy variable, 2 question items for the Purchase Decision variable, and 2 question items for the Emotional Desire variable. The data that was collected in this research was analyzed using the smart PLS 4.0 analysis tool. Results and Conclusions: the Green Marketing Strategy variable has a positive relationship and a significant influence on purchasing decisions because the P-Values value is positive and is below the 0.05 significance level, namely 0.018. Apart from that, researchers also believe that good emotional desire can strengthen the direction of this relationship because good desire can support consumers to take part in protecting the environment by paying attention to the packaging materials used, product cleanliness, whether the product is hygienic or not, and so on related to environmental sustainability. In line with the statement in the second paragraph, the results of table 3 of the second row of path efficiency show that the Emotional Desire variable can moderate the direction of the relationship between the Green Marketing Strategy variable and Purchasing Decisions because the P-Values value is positive and is below the 0.05 significance level, namely 0.000. More significant than direct testing, namely 0.017. Thus the first and second hypotheses in this research can be proven and accepted.